Apresentação - Ribeiro, Fernanda Aparecida; Marcari, Maria de Fátima Alves de Oliveira; Pinheiro, Alexandra Santos (Trem de Letras, 2016)
Apresentação do 2º volume do dossiê Literaturas de Autoria Feminina